Overfishing destroying livelihoods - Kingsley Ighobor (Africa Renewal, 2017)
It was midnight on 14 December 2016, when five fishermen in Tombo village near Freetown in Sierra Leone revved up a small outboard engine and powered their boat far out to sea. They threw in their net and soon bagged a good quantity of fish. But as they hauled in their catch, a terrible storm blew in. When the waters finally calmed, one of them, an 18-year-old named Alimamy, could not be found.